2003
DOI: 10.1103/physrevb.68.180403
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic model for the magnetization plateaus inNH4CuCl3

Abstract: A simple model consisting of three distinct dimer sublattices is proposed to describe the magnetism of NH4CuCl3. It explains the occurrence of magnetization plateaus only at 1/4 and 3/4 of the saturation magnetization. The field dependence of the excitation modes observed by ESR measurements is also explained by the model. The model predicts that the magnetization plateaus should disappear under high pressure.PACS numbers: 75.30. Cr, NH 4 CuCl 3 , TlCuCl 3 , and KCuCl 3 are isostructual quantum spin systems co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
5
18
0
Order By: Relevance
“…There is also an example of a magnet including both spinsinglet states and AFLRO which are almost decoupled. * Electronic address: HASE.Masashi@nims.go.jpIn NH 4 CuCl 3 , the spin system consists of three different S = 1/2 dimer subsystems [9]. States in two dimer subsystems are spin singlet, whereas AFLRO appears in another subsystem in low fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is also an example of a magnet including both spinsinglet states and AFLRO which are almost decoupled. * Electronic address: HASE.Masashi@nims.go.jpIn NH 4 CuCl 3 , the spin system consists of three different S = 1/2 dimer subsystems [9]. States in two dimer subsystems are spin singlet, whereas AFLRO appears in another subsystem in low fields.…”
mentioning
confidence: 99%
“…In NH 4 CuCl 3 , the spin system consists of three different S = 1/2 dimer subsystems [9]. States in two dimer subsystems are spin singlet, whereas AFLRO appears in another subsystem in low fields.…”
mentioning
confidence: 99%
“…Recently, Matsumoto [21] theoretically suggested that there are three distinct magnetic dimer sublattices with different exchange interactions in NH 4 CuCl 3 , in contrast to the isostructural KCuCl 3 and TlCuCl 3 , and reproduced well the magnetization plateaus and field dependence of the magnetic resonance frequencies observed in ESR measurements [22,23] by his model. Successive structural phase transitions which may indicate the creation of such distinct magnetic dimers have been observed at low temperatures by means of various kind of experiments [24,25,26,27,28] while the isostructural KCuCl 3 and TlCuCl 3 undergo no structural phase transitions at low temperature.…”
mentioning
confidence: 56%
“…These results imply that there are three weakly interacting distinct dimer sublattices, A, B, C, whose intradimer interactions ; respectively, to reproduce the magnetization plateaus at 1 4 and 3 4 of the saturated moment. The details will be published elsewhere [10]. As we can see in Fig.…”
mentioning
confidence: 59%